Analysis Of EMR Implementation Success Rate In RSUD Limpung Outpatient Unit Using The HOT-Fit Method - Nurul Khafidoh, Tiara; Setiono, Oki; Ratna Wulan, Widya (International Journal of Health Literacy and Science, 2025)
In organizing EMR, there are many benefits for users and for hospital services, but it has not been fully implemented. The Limpung Hospital Outpatient Unit has been implementing EMR since 2020, but during the process there are still several obstacles in implementing EMR, namely related to the features available on the system, which are considered incomplete and when there are updates or changes to new features the system often experiences downtime. The purpose of this study is to determine the extent of the success rate of RME implementation with descriptive quantitative analysis using the HOT-Fit Method. The sample was taken by total sampling which included the inclusion criteria, namely 35 officers. The results of the study for the success rate of EMR implementation on each variable, namely the Human variable gets a value of 3.00 which has a good interpretation qualification, then the Organization variable gets a value of 2.83 which has a good interpretation qualification, then the Technology variable gets a value of 2.82 which has a good interpretation qualification, and finally the Net-Benefit variable gets a value of 3.07 which has an interpr qualification. From these results, the findings highlight the importance of regular training for staff, adequate network facilities, and the development and improvements of features.